CLINICALLY ISOLATED SYNDROME IN CHILDREN AND ADOLESCENTS — RISK FACTORS FOR MULTIPLE SCLEROSIS AND PROSPECTS OF USING INTRAMUSCULAR INTERFERON β-1A - O.V. Bykova; A.N. Platonova; N.N. Shatilova; A.V. Anikin; L.M. Kuzenkova (Педиатрическая фармакология)
The first demyelinating episode in the structure of multiple sclerosis is called clinically isolated syndrome, that is the clinical debut of the disease requiring an extensive differential diagnostic search and identification of long-term therapeutic tactics. It is well-known that experience of prescribing interferon β to adult patients at this earliest stage in the disease results in a substantially improved long-term disability prognosis. At the same time, promising techniques for an early launch of the biologic response modifier therapy have not yet found sufficient application in children and adolescents with multiple sclerosis.Key words: multiple sclerosis, clinically isolated syndrome, children, adolescents, interferon β.  (Pediatric Pharmacology. – 2010; 7(3):91-94)